Influence of tail water level on the hydraulic performance of elbow draft tube - Fike, Matej (JET on-line, 2017)
Numerical simulations of the flow in the elbow draft tube of a Kaplan turbine were carried out in order to elucidate the effects of tail water level on draft tube performance and flow stability. The influence of the tail water level is explored considering the correct boundary condition at the inlet of the draft tube. It is found that the increasing tail water level affects the inlet boundary condition of the draft tube, the flow rate through the turbine, and draft tube. Thus, head recovery, efficiency and the possibility of cavitation phenomena decreases. However, the head loss increases, and the flow rate through the turbine and draft tube decrNumerical simulations of the flow in the elbow draft tube of a Kaplan turbine were carried out in order to elucidate the effects of tail water level on draft tube performance and flow stability. The influence of the tail water level is explored considering the correct boundary condition at the inlet of the draft tube. It is found that the increasing tail water level affects the inlet boundary condition of the draft tube, the flow rate through the turbine, and draft tube. Thus, head recovery, efficiency and the possibility of cavitation phenomena decreases. However, the head loss increases, and the flow rate through the turbine and draft tube decreases.
Keywords: Ansys CFX; cevi; CFD; elbow draft tube; numerical analysis; numerična analiza; računalniška dinamika tekočin; turbine